1996
DOI: 10.1002/(sici)1097-0010(199601)70:1<62::aid-jsfa465>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Phosphorus Availability: 1—In VitroStudy; Factors Affecting Endogenous Phytasic Activity and Phytic Phosphorus Content

Abstract: Phytasic activity and phytic P content, which are important factors in determining the availability of P, were measured in 56 wheat samples. The different agronomic and genetic factors which could have an influence on these two variables were studied, specifically N and/or P fertilisation, date of harvest, preharvest sprouting and variety of French wheat. Phytasic activity ranged from 206 to 775mUg−1, with an average of 508mUg−1 and a standard deviation of 109mUg−1. Only the variety of wheat appeared as a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 3 publications
3
16
0
1
Order By: Relevance
“…For example, Nour et al (2010) reported a range of 4.41-4.58 mg g -1 for three sorghum cultivars. Larsson et al (1997) reported a range of 1.3-4.0 mg g -1 for white wheat and whole wheat while Barrier-Guillot et al (1996) reported a range of 2.25-4.24 mg g -1 for 56 different wheat cultivars. This narrow range of phosphorus content shows that not only the phosphorus status of soil or fertilizer determines phosphorus contents of grains but also root uptake of phosphorus (Harrison and Dighton 1991).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Nour et al (2010) reported a range of 4.41-4.58 mg g -1 for three sorghum cultivars. Larsson et al (1997) reported a range of 1.3-4.0 mg g -1 for white wheat and whole wheat while Barrier-Guillot et al (1996) reported a range of 2.25-4.24 mg g -1 for 56 different wheat cultivars. This narrow range of phosphorus content shows that not only the phosphorus status of soil or fertilizer determines phosphorus contents of grains but also root uptake of phosphorus (Harrison and Dighton 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Work on wheat NSP has been more recent and mainly centred around the way in which NSP influence the rheological properties of dough [8,22,28,31]. Viscosity studies have been carried out by Saulnier et al [29], and studies on the effect of the genotype on cell wall content and phytase activity have also been performed recently [5,6,9]. No The applied viscosities were measured according to the protocol used by Carré et al [13].…”
mentioning
confidence: 87%
“…In consequence, the phytic acid phosphorus is not available and, in regions where there is a high concentration of intensive indoor animal production, it contributes to the pollution of surface water. Wheat, on the other hand, contains plant phytase whose activity varies depending on the variety [5,6,30]. This phytase is activated during digestion and liberates a substantial amount of the grain phosphorus [18].…”
mentioning
confidence: 99%
“…The concentration of PP within the same ingredient can vary considerably. Barrier-Guillot et al [69] found that the concentration of PP ranged from 0.092% to 0.268% dry matter (DM) in wheat and depended on soil fertility, plant variety, and stage of plant maturity at harvest.…”
Section: Plant Feedstuffsmentioning
confidence: 99%